Analisis Kebutuhan Jenis Fasilitas Penyeberang Jalan Berdasarkan Gap Kritis (Studi Kasus PT. Sido Muncul Ungaran – Jawa Tengah) - Siwanto, Joko; Teguh, Julianto (Department of Civil Engineering, Diponegoro University, 2008)
The type of pedestrians crossing facility provided for employees along the street Ungaran - Bawen hasn’t been same and its use isnot efficient since there are still any cases appeared either for the pedestrians crossing the street or traffic flow generally. The aim of the study is to evaluate the work of pedestrians crossing facility, that is zebra cross from the side of analysis on critical gap for finding out the opportunity in crossing the street safety and donot disturb the passing vehicles. This analysis method of critical gap is used for searching the minimum gap among vehicle passing through location in order that the pedestrian crossing the street may cross safety. Primary data taking is carried out through field survey using handycam for watching the conflict point and time gap between vehicles passing through the street and pedestrian who cross the street to the conflict point. From the data analysis result, the writer obtains that critical gap in study location is 2,62 second and the opportunity degree for crossing the street safety is only 11 persons on 6.30 to 7.30 WIB and 7.30 to 8.30 as much as 29 persons. Thus, we may conclude that pedestrian crossing facility, namely zebra cross is not effective and for the further is that pedestrian crossing should not be in the same field. Keywords: Zebra Cross, AnalysisPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3690[How to cite: Siswanto, J. dan Teguh, J. (2008), Analisis Kebutuhan Jenis Fasilitas Penyeberang Jalan Berdasarkan Gap Kritis (Studi Kasus PT. Sido Muncul Ungaran – Jawa Tengah), Jurnal Media Komunikasi Teknik Sipil, Tahun 16, Nomor 2, pp. 148-159]